Explores Javanese Culture-Based Character Education Kraton Kasunanan Surakarta - Ikhsan Faturohim; Triyanto Triyanto; Joko Daryono (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
The Indonesian people greatly emphasize Javanese culture and its role in preserving the environment. To support student growth, this study recommends prioritizing culture-based educational practices that align with national values, particularly at the elementary level. At SDN Kasatriyan Surakarta, the application of Javanese culture is integrated into teaching, intracurricular and extracurricular activities, and overall school culture. This approach enables students to develop character education values like simplicity (gumregah), hard work, cooperation (gotong royong), independence (ning rat ning set rules), and environmental concern (sahatmaka). Qualitative research drawing on interviews and observations underscores the value of Javanese culture-based education at the elementary level. The research shows that implementing such a program at Kraton Kasunanan Surakarta positively impacts student character development. The active involvement of educators is key to successful program implementation, as demonstrated by students' high level of engagement in learning activities and their success in various competitions.